Pemanfaatan Permainan Bahasa Menjadi Produk Usaha Kaos Berbasis Bisnis Kata di Kelompok Karang Taruna Desa Parangargo Kecamatan Wagir Kabupaten Malang untuk Mendukung Ekonomi Kreatif - Kingkin Puput Kinanti; Endang Setiyo Astuti; Dwi Ulfa Nurdahlia (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2019)
The activities of Society Partnership Program (PKM) was carried out together with the youth organization of Karang Taruna MAATOON in Parangargo village, Wagir sub district, Malang Regency. The purposes of the activities are 1) to empower the youth to become entrepreneurs and get involved in developing creative economy, 2) to develop the skill of designing words, phrases, and sentences used to produce saleable word-based T-shirts, like Dagadu and Joger, 3) to facilitate the Karang Taruna in producing and marketing the products. In order to achieve the purposes, on the aspects of production and management, some trainings and workshops have been already done, such as training of word designing through Corel Draw application and workshop of finance management and digital marketing. These activities of Society Partnership Program (PKM) were done in stages, namely preparation, program planning, implementation, and evaluation.